Genome-wide sequence divergence of satellite DNA could underlie meiotic failure in male hybrids of bighead catfish and North African catfish (Clarias, Clariidae) - Lisachov, Artem; Panthum, Thitipong; Dedukh, Dmitrij; Singchat, Worapong; Ahmad, Syed Farhan; Wattanadilokcahtkun, Pish; Thong, Thanyapat; Srikampa, Phanitada; Noito, Kantika; Rasoarahona, Ryan; Kraichak, Ekaphan; Muangmai, Narongrit; et al. (Genomics, 2024)
Hybrid sterility, a hallmark of postzygotic isolation, arises from parental genome divergence disrupting meiosis. While chromosomal incompatibility is often implicated, the underlying mechanisms remain unclear. This study investigated meiotic behavior and genome-wide divergence in bighead catfish (C. macrocephalus), North African catfish (C. gariepinus), and their sterile male hybrids (important in aquaculture). Repetitive DNA analysis using bioinformatics and cytogenetics revealed significant divergence in satellite DNA (satDNA) families between parental species. Notably, one hybrid exhibited successful meiosis and spermatozoa production, suggesting potential variation in sterility expression. Our findings suggest that genome-wide satDNA divergence, rather than chromosome number differences, likely contributes to meiotic failure and male sterility in these catfish hybrids.
Keywords: Chromosome pairing; Synaptonemal complex; Infertility, Male; meióza; sumci; mužské pohlaví; Hybrid sterility; DNA, Satellite; satelitní DNA; Genome; Immunostaining; zvířata; Catfishes; Meiosis; nemoci ryb; Hybridization, Genetic; genom; hybridizace genetická; Clariid catfish; mužská infertilita; Fish Diseases; Africa, Northern; severní Afrika; Male; Animals